New Insights into Food Fermentation - Bernini, Valentina; Lindner, Juliano De Dea (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is dedicated to new insights into food fermentation. The goal of this reprint was to broaden the current knowledge on advanced approaches concerning food fermentation, gathering studies on conventional and unconventional food matrix fermentation, functional compounds obtained through fermentation, fermentations increasing quality and safety standards, as well as papers presenting innovative approaches shedding light on the microbial community that characterizes fermented foods.